Morphometric, meristic and growth pattern of Osphrenemus gouramy Lac. from the Pinang Luar Oxbow Lake, Buluhcina Village, Kampar Regency, Riau - Mirnawati Dewi; Deni Efizon; Eddiwan ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Osphrenemus gouramy or gurami fish is freshwater fish that live in thePinang Luar Lake. Population of that fish in the lake, however, is low andinformation on its biological aspect such as morphometric, meristic, and growthpattern is rare. A study aims to determine those aspects had been conducted inMarch 2017. There were 102 fishes, with 63.87-193.72 mm TL and 3.49-129.98gr BW. There were 25 morphometrical characteristics measured and 11 meristicalcharacteristics counted. The meristical characteristic of this fish as as follow :D.10-14, P.9-13, V.1-6, A.19-20, C.15-16, and the number of scales in the predorsalfin was 21-80, around the body was 37-76, in the caudal penducle was 8-31and in the lateral line was 20-42. The length-weight relationship shown thatgrowth pattern of the fish is positif allometric, b=3.070 in male, and b=3.032 infemale. The water quality parameters shown that temperature 27-29 oC,transparancy 36-42 cm, pH 5, DO 2-2.5 mg/L, CO2 6.9-7 mg/L and depth 150-520cm. Data on water quality parameters indicate that water quality in the PinangLuar Lake is able to support the life of gurami fish.Keywords: growth patterns, meristic, morphometric, Osphrenemus gouramy,Pinang Luar Oxbow Lake.